Experimental simulation of stationary and traveling density-driven thunderstorm downbursts using the two-fluid model. Issue 211 (April 2021) - Babaei, Rose; Graat, Kyle; Chan, Calvin; Savory, Eric
Abstract: In the present study, novel release mechanisms were developed for laboratory simulations of density-driven downbursts using the two-fluid model. The ability of these new designs in producing repeatable outflows was examined and the influence of minimizing the release cylinder wall effect was tested. The entire experimental setup was also modified to simulate the effect of translation on the resultant downburst wind flows. Planar laser induced fluorescence (PLIF) technique was utilized to visualize the flows and to provide quantitative scalar (density) field data. The results from this study showed a clear difference between the flow fields arising from the two release mechanisms, namely, a higher degree of mixing with ambient fluid, lower downward speed and higher radial propagation rate at the early stages of the simulated downburst lifecycle for the porous wall cylinder. The outflows of stationary and traveling downbursts were compared and the differences between their flow fields and propagation rates were elaborated; for the shear flows tested, a linear relationship between the downburst displacement and storm translation velocity was obtained. The radial outflows of the simulated downbursts were compared to the empirical gravity currents and the mixing of downburst and ambient fluids was quantified using calibrated PLIF images. Highlights: New method for experimental simulation of density-driven downbursts validated. Effects of storm translation and ambient wind flow incorporated. Outflow data may be fitted to an empirical gravity current model. Influence of translation on downburst footprint at the ground determined. Translation effect on time-history of average downburst fluid density quantified.